Initier un pair à une nouvelle pratique professionnelle - Samira Mahlaoui (Éducation et Socialisation)
The article is interested in an original experiment of transmission involving trainers of the agricultural education in situation of initiation towards peers to make them acquire and operate a new know-how regarding formalization of their educational practices. This formalization takes the shape of learning scenarios realized within the framework of a system computerized by exchange and by mutualization called Ersce—national exchange of resources staged for the local development of the distance education. It is also a question of proposing to all the trainers of the domain a medium of knowledge on their educational activities. The methodological frame of the auto-confrontations (Clot & Faïta, 2000) to which we resort permits a better understanding of the transmission of the ‘knowledge to formalize’ in game, but also the potential development of this transmission at the individual and collective levels.